Quantitative Estimation of Plumbagin in Various Parts of Plumbago rosea and Plumbago zeylanica - SHEEJA*, EDWIN; JOSHI, S.B.; JAIN, D.C. (Asian Journal of Chemistry, 2009)
In this work, the various parts of Plumbago rosea and Plumbagozeylanica have been standardized by estimating plumbagin. The driedplant materials were subjected to successive solvent extraction (petroleumether (60-80 ºC), chloroform, acetone, ethanol and aqueous). Theextracts that showed positive qualitative test were further taken for theestimation of plumbagin through HPTLC. The results indicated theconcentration of plumbagin in the following manner, P. rosea root >P. zeylanica root > P. rosea stem > P. zeylanica stem> P. rosea leaf >P. zeylanica leaf.